Evaluasi Program Pemberdayaan Masyarakat dalam Pembinaan Industri Rumah Tangga Oleh Dinas DP3AKB di Kota Cilegon - Indi Rahmawati; Nabilla Putri Wahyuni; Ayu Laras Gouvany; Andini Nur Fitriya (Peneliti.net, 2022)
Graphically from the Cilegon City BPS report, it states that the level of welfare of the Cilegon people has a good average, but it cannot be denied that there are still some people who still live below the poverty line. Related to this, the City Government of Cilegon, which includes the DP3AP2KB Office, provides a solution by providing various types of training in various fields, one of which is the development of home industry. As for this evaluation, it aims to assess the success of the industrial development program organized by the DP3AP2KB Office through the CIPP evaluation model. The evaluation method used is the interview method. The data sources used in this evaluation came from two sources, namely primary data sources obtained from the DP3AP2KB Office, instructors, and coaching participants; as well as secondary data sources derived from literature and documentation relevant to the research. The research instruments used were interview guides, observations, and documentation. The data analysis technique used is qualitative data analysis through data collection, reduction, data display, and drawing conclusions